KEMITRAAN BIDAN DENGAN DUKUN BAYI DI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Sri Wiranti; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Research on midwife partnership with TBAs in the District of Indragiri Hulu Seberida. This research was conducted in all of the village and the villages in the district Seberida. The formulation of the problem in this study is How Implementation and Obstacles encountered in partnership with Shaman Baby Midwife in District seberida Indragiri Hulu. In this study, the author uses descriptive quantitative method, performed by acquiring and analyzing data in the form of numbers. This method as a process of solving problems examined by explaining the state of an object of research is based on facts. To obtain the necessary data, the authors conducted observation in the study site to the TBAs and midwives in collaboration with PHC Pangkalan Kasai in all rural and urban villages in Sub Seberida Indragiri upstream and conduct interviews with relevant parties, namely the Head of Puskesmas Pangkalan Kasai and Chief Medical Officer of Indragiri Hulu. The results showed that the midwife partnership with TBAs in District seberida already well underway. But the midwife partnership with TBAs in District Seberida there are still some obstacles which are still there TBAs are no longer cooperate with the midwife and there are still people who believe aid delivery to the village midwife because of kepercayaa, customs and economy.Keywords: Partnership, midwives, TBAs.